2014
DOI: 10.1007/s00418-014-1216-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of estrogen receptors α and β and G-protein-coupled estrogen receptor 1 in the human testis

Abstract: Estrogen signaling is considered to play an important role in spermatogenesis, spermiogenesis and male fertility. Estrogens can act via the two nuclear estrogen receptors ESR1 (ERα) and ESR2 (ERβ) or via the intracellular G-protein-coupled estrogen receptor 1 (GPER, formerly GPR30). Several reports on the localization and expression of all three receptors in the human testis have been published but are controversial particularly in case of ERα. Contrary to previous studies, we decided therefore to evaluate exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 55 publications
0
31
1
Order By: Relevance
“…1a). These results are in part different from data on GPER gene expression, which was observed weakly in Sertoli cells and higher in interstitial cells [6]. The GPER protein of 42 KDa was retrieved on human spermatozoa, in the mid-piece (Fig.…”
Section: Oestrogencontrasting
confidence: 81%
See 1 more Smart Citation
“…1a). These results are in part different from data on GPER gene expression, which was observed weakly in Sertoli cells and higher in interstitial cells [6]. The GPER protein of 42 KDa was retrieved on human spermatozoa, in the mid-piece (Fig.…”
Section: Oestrogencontrasting
confidence: 81%
“…1a; for review [1, 4, 5]). Recently, in situ hybridisation and immunohistochemistry experiments on human testis confirmed ESR1 and ESR2 expression in germ cells, ESR1 expression in interstitial cells and ESR2 expression in Sertoli cells [6]. In addition, some variants have been found.…”
Section: Oestrogenmentioning
confidence: 99%
“…The primary source of this hormone is from the aromatization of testosterone1. Estrogen receptors alpha and beta (ERα and ERβ), together with the membrane associated G-protein-coupled functional ER (GPER), and the enzyme cytochrome P450 aromatase, which converts testosterone to estrogen, are abundant within the testis234. Estradiol is produced in immature germ cells, spermatozoa, in the epithelium of the efferent ductules and the proximal epididymal duct and in the Leydig cells and Sertoli cells56789.…”
mentioning
confidence: 99%
“…In the human testis, both ERα and ERβ mRNA and protein have been localized to the germ cells (ERβ>ERα), ERβ but not ERα localized to the sertoli cells, and mRNA for the intracellular G-protein-couple estrogen receptor 1 (GPER) as well as ERα protein (but not mRNA) localized to the interstitial cells. Overall, these authors reported that RT-PCR analysis indicated that germ cell expression of ERα is weak, that sertoli cell expression of ERβ is moderate, and that interstitial cell expression of GPER is strong, with their in situ hybridization and immunohistochemical analyses confirming ERα and ERβ in germ cells, ERβ and GPER in Sertoli cells, and GPER in interstitial (leydig) cells [52]. Continuing with the human testis, androgen receptor (AR) protein is predominantly localized to the sertoli cells, with the level of expression for this receptor dependent upon the stage of the spermatogenic cycle [53].…”
Section: Discussionmentioning
confidence: 90%